1997
DOI: 10.1177/0310057x9702500609
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Sevoflurane with Halothane for Paediatric Day Case Surgery

Abstract: A phase III, open label, randomized study was conducted in 50 patients comparing halothane and sevoflurane for paediatric day case surgery. A graded inhalational induction resulted in only slightly more rapid induction with sevoflurane (3.34±0.92 versus 3.85±1.02 minutes; P>0.05). In children receiving sevoflurane, systolic blood pressure decreased to a lesser extent during induction (14.3±19.2 versus 26.9±10.9 percent decrease from resting values; P<0.01) and heart rate was maintained. Respiratory events (cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 16 publications
(26 reference statements)
1
26
1
1
Order By: Relevance
“…20 A similar model with isoflurane has not been evaluated, but isoflurane is known to irritate the upper airway in children. 16,21,22 Furthermore, we removed the LMA at a deep level of anesthesia, a maneuver that has been associated with fewer adverse airway events than its removal in the awake state. 16,23 This may have further decreased the difference in the rates of adverse airway events between the 2 treatments.…”
Section: Discussionmentioning
confidence: 99%
“…20 A similar model with isoflurane has not been evaluated, but isoflurane is known to irritate the upper airway in children. 16,21,22 Furthermore, we removed the LMA at a deep level of anesthesia, a maneuver that has been associated with fewer adverse airway events than its removal in the awake state. 16,23 This may have further decreased the difference in the rates of adverse airway events between the 2 treatments.…”
Section: Discussionmentioning
confidence: 99%
“…14 There is now some evidence that sevoflurane may be associated with even fewer airway complications such as laryngospasm and coughing than halothane. 15 If deepening anaesthesia fails and muscle relaxation is required, suxamethonium is the current agent of choice for its rapidity of both onset and offset. The dose required can be as little as 0.1 mg/kg IV.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, objective pain/discomfort scores during the first 30 to 40 minutes in the recovery room were significantly [74,88] or markedly (statistical analysis not reported) [81,83] higher in sevoflurane than in halothane recipients.…”
Section: Postoperative Painmentioning
confidence: 99%
“…In a few studies the times to induction [81,86] or emergence [82,87] were similar between treatment groups and 1 study found a longer time to recovery with sevoflurane. [89] …”
Section: Sevoflurane Versus Halothanementioning
confidence: 99%
See 1 more Smart Citation